Sustainability Analysis of Electricity Generation in Colombia through the Projection of Energy Efficiency Indicators - Valencia-Duque, Melissa; Zapata-Mina, Juan; Tibaquirá, Juan E.; Castillo, Juan Carlos (International Journal of Energy Economics and Policy, 2023)
The objective of this study is to determine whether current electric power generation practices in Colombia will cover future electricity demand in a sustainable manner. For this purpose, a projection of a current trend scenario was made using the Autoregressive Vectors model, and the results were compared with the projected electricity demand for the country to the year 2030. An analysis of generation efficiency as a technical indicator, of primary energy intensity as an economic indicator, and of carbon emission intensity as an environmental indicator was carried out. It was identified that starting in 2025, electricity generation will not be able to cover the country's electricity demand at its upper limit, and by 2030 demand will exceed generation in its medium scenario. Therefore, it is advisable to implement energy efficiency strategies that will either reduce end-user electricity demand or increase electricity generation by 2025. On the other hand, the country's electricity generation process tends to increase its η and reduce both its IEP and IEC by 2030, which indicates that the rate of improvement of electricity generation practices in Colombia, which is implicit in the historical data analyzed, will be sufficient to achieve sustainable generation in the future.